SATLOGI SANTRI SEBAGAI SISTEM NILAI DAN FALSAFAH HIDUP PESANTREN ZAINUL HASAN GENGGONG PROBOLINGGO - Herwati Herwati (LP2M Universitas Ibrahimy, 2021)
Moral decadence is a common thing among Islamic boarding schools in the archipelago. Violating ethical values which results in the degeneration of santri morals, obedience to kiai being ignored, western cultural civilization that promotes individual freedom has become a common phenomenon at Pesantren Zainul Hasan Genggong. As a solution, the Santri Satlogi was initiated by the 3rd caretaker of Pesantren Zainul Hasan Genggong KH. Hasan Saifourridzal. The Santri Satlogi are the philosophical values of the Zainul Hasan Genggong Islamic Boarding School which were formulated on 17 August 1989 M. Ridlallah, and Ikhlas Lilahi Ta'ala with the aim that students and alumni in addition to mastering science, also to have the identity of students who can practice knowledge that is practical in everyday life so that they can become role models for the ummah to give the best in life in the community.